2008
DOI: 10.1029/2007gl032980
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and anthropogenic controls of topsoil features in the semi‐arid East Asian steppe

Abstract: Topsoil characteristics and their determinants in the steppe on the central Inner Mongolian Plateau were investigated. Percentages of different grain size fractions of topsoil samples from 236 plots and corresponding standardized data of four environmental/human‐activity factors, namely mean annual temperature (MAT), mean annual precipitation (MAP), human disturbance index (HDI) and land use/land cover (LULC) types were used to perform canonical correspondence analysis (CCA). The roles of both human land uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…In arid and semi-arid ecosystems experiencing increasing aridity, soils become more vulnerable to wind erosion because vegetation coverage declines (Zhang and Liu, 2010). Similar to our results, Liu et al (2008) found that sand fractions in soils of steppe and meadow were negatively correlated with MAP and positively correlated with MAT due to drought-driven vegetation cover decline in the semi-arid East Asian steppe.…”
Section: Discussionsupporting
confidence: 80%
“…In arid and semi-arid ecosystems experiencing increasing aridity, soils become more vulnerable to wind erosion because vegetation coverage declines (Zhang and Liu, 2010). Similar to our results, Liu et al (2008) found that sand fractions in soils of steppe and meadow were negatively correlated with MAP and positively correlated with MAT due to drought-driven vegetation cover decline in the semi-arid East Asian steppe.…”
Section: Discussionsupporting
confidence: 80%
“…MAT, MAP and a human disturbance index (HDI) were selected as environmental variables. The calculation of HDI was based on plant species composition in each plot (Liu et al. , 2006, 2008a, b).…”
Section: Methodsmentioning
confidence: 99%
“…First, an importance value (IV) was calculated for each species in each sample based on the sum of its relative abundance, relative coverage and relative height. Second, all species were divided into three groups, and weighted based on the different degree of vegetation degradation and human disturbance as 1/3 (Group I), 2/3 (group II) and 1 (Group III), respectively (Liu et al. , 2006, 2008a, b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most human effects on semi-arid climates are related to agricultural exploitation of lands. Introduction of agriculture into such areas, whose natural condition is already agriculturally marginal, might be motivated by a number of economic or social factors (Liu et al 2008). These factors include the need to provide food for a larger population, the decreasing productivity of existing agricultural land, and the profit motive.…”
Section: Introductionmentioning
confidence: 99%